2022
DOI: 10.4274/ejbh.galenos.2021.2021-11-1
|View full text |Cite
|
Sign up to set email alerts
|

What Has Changed During the COVID-19 Pandemic? - The Effect on an Academic Breast Department in Portugal

Abstract: Introduction: One year ago, Portugal entered its first lockdown because of the coronavirus disease-2019 (COVID-19) pandemic. The impact of this on delays in cancer diagnosis and treatment is a major concern, which may negatively affect the outcomes of these patients. Materials and Methods:This retrospective, single-center analysis compared the clinical and pathological characteristics of breast cancer (BC) patients referred to a medical oncology first appointment between March 2020 and 2021, with the same peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
1
5
0
1
Order By: Relevance
“…Many studies discussed the changes in staging trends before and after the pandemic. 12,2628 A study conducted in the United Kingdom by Borsky et al reported an increase in node-positive disease on presentation in 2020 compared to 2019 (36.2% vs. 23.6%, p = 0.0063), an increase in metastatic disease at presentation (8.0% vs. 2.9%, p = 0.0295) and increased in median UICC TNM stage at detection from 1b to 2a ( p = 0.0184). Conversely, a Turkish study by Kara et al did not find any statistically significant differences in tumor size, nodal involvement, or overall TNM stage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies discussed the changes in staging trends before and after the pandemic. 12,2628 A study conducted in the United Kingdom by Borsky et al reported an increase in node-positive disease on presentation in 2020 compared to 2019 (36.2% vs. 23.6%, p = 0.0063), an increase in metastatic disease at presentation (8.0% vs. 2.9%, p = 0.0295) and increased in median UICC TNM stage at detection from 1b to 2a ( p = 0.0184). Conversely, a Turkish study by Kara et al did not find any statistically significant differences in tumor size, nodal involvement, or overall TNM stage.…”
Section: Discussionmentioning
confidence: 99%
“…6 In a subsequent study conducted in Portugal, the number of patients with advanced forms of BC who were admitted for the first time decreased by 40%. 12 Another multi-institutional study found a decrease in BC screenings and diagnosis during the COVID-19 pandemic with a change in disease staging distribution, with more patients diagnosed with stage IIB and IV during the pandemic. 13…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outro estudo, com dados do Reino Unido, encontrou, durante a pandemia, aumento significante do estágio da doença à apresentação inicial, bem como dos casos com acometimento linfonodal e doença metastática 25 . Já em um centro de Portugal houve aumento significante na proporção de pacientes admitidas pela primeira vez para terapia sistêmica com câncer de mama metastático 26 .…”
Section: Região Mês 2021 Jan Fev Mar Abr Maiunclassified
“…45 Other studies in the US, South America, Europe, the Middle East, and Asia, obtained similar results. [12][13][14]30,43,[46][47][48][49] Studies showing no tumor shift, as displayed in the presented results, are scarce, 11,15 but may also have been underreported. Our study showed no difference in terms of frequency and modalities of breast reconstruction surgery in 2020 compared to 2019, unlike other studies that found less breast reconstruction surgeries post-pandemic, in consistence with scientific recommendations.…”
mentioning
confidence: 93%